2022
DOI: 10.3847/2041-8213/ac531f
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Cold-stream to Hot-accretion Transition as Traced by Lyα Emission from Groups and Clusters at 2 < z < 3.3

Abstract: We present Keck Cosmic Web Imager observations of giant Lyα halos surrounding nine galaxy groups and clusters at 2 < z < 3.3, including five new detections and one upper limit. We find observational evidence for the cold-stream to hot-accretion transition predicted by theory by measuring a decrease in the ratio between the spatially extended Lyα luminosity and the expected baryonic accretion rate (BAR), with increasing elongation above the transition mass (M stream). This implies a modu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 48 publications
3
38
0
Order By: Relevance
“…ID9316 is a bright submm galaxy close to a galaxy group RO0959 at z = 3.1 (Daddi et al 2022), and was proposed to be at z > 7 by Oteo and collaborators (see ALMA proposal ID: 2018.1.00874.S, PI: I. Oteo) and was observed with ALMA standard line scans in band 3. Meanwhile, this galaxy has also snapshot imaging in ALMA band 6 (ID: 2013.1.00118.S, PI: M. Aravena) and band 7 (ID: 2016.1.00478.S, PI: O. Miettinen).…”
Section: Sample Observations and Data Reductionmentioning
confidence: 97%
“…ID9316 is a bright submm galaxy close to a galaxy group RO0959 at z = 3.1 (Daddi et al 2022), and was proposed to be at z > 7 by Oteo and collaborators (see ALMA proposal ID: 2018.1.00874.S, PI: I. Oteo) and was observed with ALMA standard line scans in band 3. Meanwhile, this galaxy has also snapshot imaging in ALMA band 6 (ID: 2013.1.00118.S, PI: M. Aravena) and band 7 (ID: 2016.1.00478.S, PI: O. Miettinen).…”
Section: Sample Observations and Data Reductionmentioning
confidence: 97%
“…Highlights of recent research include discoveries of enormous Ly𝛼 ★ E-mail: rhythm.shimakawa@nao.ac.jp † NAOJ Fellow nebulae (ELANe) around luminous radio-quiet quasars, defined as Ly𝛼 nebulosities with particularly high surface brightness spreading beyond hundreds pkpc (Cantalupo et al 2014;Hennawi et al 2015;Cai et al 2017Cai et al , 2018Arrigoni Battaia et al 2018). Such extreme cases extending beyond the virial radius allocated an exclusive role as a probe of the underlying large-scale structures at high spatial resolution (see also Erb et al 2011;Fumagalli et al 2016;Umehata et al 2019;Kikuta et al 2019;Daddi et al 2021Daddi et al , 2022. Discoveries of ELANe also suggested that cool gas components are more enriched over the IGM scale in and around massive haloes at high redshifts than previously considered.…”
Section: Introductionmentioning
confidence: 89%
“…To determine redshifts, the target SMGs are grouped into three categories: SMGs with multiple line detection, those with only one line detection, and those that do not have emission line detection. Other works in the literature are referenced to aid the redshift determinations, in particular those from Jiménez-Andrade et al (2020), Mitsuhashi et al (2021), andDaddi et al (2022). The category to which each SMG belongs is given in Table 1.…”
Section: Redshift Determinationmentioning
confidence: 99%